Using Gather Town in Critical Reading Arabic: An Attempt to Overcome the Weaknesses of Online Learning - Bahtiar, Ihwan Rahman; Nuruddin, Nuruddin; Barnabas, Raden Ahmad; Jubaidah, Siti; Ilham, Andri; Nafi'ah, Khotimatun (LPPM Universitas Bina Bangsa, 2025)
As online learning continues to be implemented post-pandemic, the use of video conferencing applications in higher education remains high. Some research shows that video conferencing, such as Zoom and Google Meet, has a positive impact on the online learning process. However, video conferences can only partially bring the natural atmosphere into the virtual classroom. As one of the video conferencing platforms, Gather Town offers new features that can create a virtual classroom atmosphere like a real class. This study aims to describe online lecture activities using Gather Town and students' perceptions of the application. The results show that Gather Town is easy to use and offers a new atmosphere in online learning. The results of student perceptions also show that Gather Town is easy to use, can inspire motivation and interest in education, is applicable, stimulates critical thinking and problem-solving skills, and is consistent with real-world contexts and student characteristics.